Reliability and Validity of the Japanese Version of the Physical Activity Questionnaire for Older Children. (March 2019) - Isa, Tsunenori; Sawa, Ryuichi; Torizawa, Kohtaroh; Murata, Shunsuke; Saito, Takashi; Ebina, Aoi; Kondo, Yuki; Tsuboi, Yamato; Fukuta, Akimasa; Misu, Shogo; Ono, Rei
Objectives: This study aimed to examine the reliability and validity of the Japanese version of the Physical Activity Questionnaire for Older Children (PAQ-C) in Japanese children aged 9 to 12 years. Methods: A total of 210 children aged between 9 and 12 years participated. Internal consistency and test-retest reliability were evaluated using Cronbach alpha coefficient and intraclass correlation coefficient (ICC), respectively. Validity was evaluated using athletic competence (AC), self-efficacy (SE), body mass index (BMI), body fat percentage (%BF), cardiovascular fitness (CVF), and World Health Organization Health Behavior in School-aged Children (WHO HBSC) physical activity questionnaire. Results: Internal consistency was acceptable (alpha = 0.80) and test-retest reliability showed excellent agreement (ICC = 0.83). The PAQ-C score was significantly correlated with AC ( r  = 0.41), SE ( r  = 0.65), %BF ( r  = 0.19), and CVF ( r  = −0.32). The PAQ-C score of the active group classified by the WHO HBSC physical activity questionnaire (mean score ± standard deviation [SD] = 3.03 ± 0.57) was significantly higher than that of the inactive group (mean score ± SD = 2.27 ± 0.63, P  < .01). Conclusions: The PAQ-C had acceptable reliability and validity. The PAQ-C is a useful instrument to evaluate physical activity for Japanese children aged 9 to 12 years.